2019
DOI: 10.1021/acsinfecdis.9b00154
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Protein–Protein Interface Inhibitors Allow Efficient Inhibition of Type III Secretion Machinery and Pseudomonas aeruginosa Virulence

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen naturally resistant to many common antibiotics that acquires new resistance traits at an alarming pace. Targeting the bacterial virulence factors by an anti-virulence strategy therefore represents a promising alternative approach besides antibiotic therapy. The Type III Secretion System (T3SS) of P. aeruginosa is one of its main virulence factors. It consists of more than 20 proteins building a complex syringe-like machinery enabling the injection of toxin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Recent studies have identified fungal-specific T6SS effector proteins (Tfe1 and Tfe2) in another Gram-negative opportunistic bacteria Serratia marcescens [154,155]. These effector proteins contributed to T6SS-mediated inhibition of fungal growth in the fungal species Candida albicans, Candida glabrata, and Saccharomyces cerevisiae [154,155]. Effector-based antifungal activity was also reported for P. aeruginosa T6SS protein Tse2, which showed toxic effects and inhibition of growth in the yeast Saccharomyces cerevisiae [156].…”
Section: Role Of Secretion Systems In P Aeruginosa Virulence and Quorum-sensing Responsementioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies have identified fungal-specific T6SS effector proteins (Tfe1 and Tfe2) in another Gram-negative opportunistic bacteria Serratia marcescens [154,155]. These effector proteins contributed to T6SS-mediated inhibition of fungal growth in the fungal species Candida albicans, Candida glabrata, and Saccharomyces cerevisiae [154,155]. Effector-based antifungal activity was also reported for P. aeruginosa T6SS protein Tse2, which showed toxic effects and inhibition of growth in the yeast Saccharomyces cerevisiae [156].…”
Section: Role Of Secretion Systems In P Aeruginosa Virulence and Quorum-sensing Responsementioning
confidence: 95%
“…The HSI-I and HSI-II loci have been implicated in P. aeruginosa-mediated pathogenesis in progressive lung diseases [153]; HSI-III has also been identified as an essential component for bacterial virulence [148]. Recent studies have identified fungal-specific T6SS effector proteins (Tfe1 and Tfe2) in another Gram-negative opportunistic bacteria Serratia marcescens [154,155]. These effector proteins contributed to T6SS-mediated inhibition of fungal growth in the fungal species Candida albicans, Candida glabrata, and Saccharomyces cerevisiae [154,155].…”
Section: Role Of Secretion Systems In P Aeruginosa Virulence and Quorum-sensing Responsementioning
confidence: 99%
“…Cytotoxic potential of the P.a clinical isolates on eukaryotic cells was tested according to previously described protocols [73,74], with slight modifications. Antibiotic resistance phenotypes were tested following the recommendations of the European Committee for Antimicrobial Susceptibility Testing 2017 criteria [75].…”
Section: Phenotypic Assaysmentioning
confidence: 99%
“…Finally, a different group used a clever set of ELISAs featuring PscE and PscG as "bait" and signal (106). Compounds that bound to the bait protein and prevented the formation of the heterodimer were then combined using synthetic chemistry approaches to develop larger, more complex molecules with increased affinity and efficacy, an approach that is increasingly commonly used in the development pipeline for drugs coming from fragment-based screening (34).…”
Section: Toxin Secretion Systemsmentioning
confidence: 99%